Area and isolation influence on bird diversity in Eucalyptus plantations: An island biogeography perspective - José A. Oddi; Aldana M. Ariza; Julieta Filloy (Frontiers of Biogeography)
We explored how patch area and isolation from a mainland affect biodiversity distribution patterns in anthropogenic monocultures resembling habitat islands and surrounded by a structurally contrasting matrix. Grassland afforestation with Eucalyptus plantations ongoing in Río de la Plata grassland provides a valuable opportunity to study how these spatial features relate to forest mainland-related taxonomic and functional diversity. We sampled birds in 17 Eucalyptus plantations located in eastern Entre Ríos province, in Argentina, using the point count technique. We measured patch area and distance from a forest mainland. We also recorded vegetation structure variables within plantations to control for the potential influence of habitat structural complexity. We analyzed the relationships between the spatial attributes of plantations (area and isolation) and species richness, functional richness, and functional originality using generalized linear models (GLMs) and Analysis of Deviance. Plantation area held no influence whatsoever on either taxonomic or functional diversity of forest birds inhabiting plantations. In contrast, we found distance to the nearest riparian forest to negatively affect species richness, functional richness, and functional originality of forest birds in Eucalyptus plantations. Unlike most natural habitat islands, traditional species–area relationship patterns seem to be hindered in strictly managed anthropogenic monocultures, probably due to the lack of a strong link between patch area and habitat diversity, and forest bird functional diversity was also not related to patch area. Instead, our study suggests that in anthropogenic monocultures isolation from a mainland promotes less diverse and more redundant assemblages. Highlights We adopted an island biogeography approach to study bird biodiversity patterns in Eucalyptus plantations embedded within agricultural-pastoral grasslands. Unlike natural habitat islands, plantation size had no influence on forest bird diversity, challenging traditional species–area relationship patterns. Distance from the natural forest mainland negatively affected both taxonomic and functional diversity of forest bird communities. Isolation from natural forests led to more functionally redundant bird assemblages in Eucalyptus plantations.